How information processing and mobile channel choice influence product returns: An empirical analysis. Issue 3 (13th November 2018) - Seeger, Marie K.; Kemper, Jan; Brettel, Malte
Abstract: The mobile internet is starting to overtake the desktop device‐based internet as a purchase channel. Its impact on consumer behavior is therefore increasingly important to understand. This study seeks to understand and measure, if usage of mobile devices for online purchases leads to a lower decision quality and, in effect, to more product returns. In doing so, the impact of information environments on the end‐to‐end consumer purchase decision‐making process is better understood and it is investigated, if the information environment of mobile devices leads consumers to take more error‐prone purchase decisions. An exclusive data set spanning more than 140 million transactions of a European online retailer is used to empirically analyze changes in product return behavior after mobile channel adoption. The results show that mobile channel usage is positively related to product returns, overall and for both, purchases made with mobile devices and purchases made with desktop devices, although prior literature predicts that returns from desktop purchases should not increase. These findings suggest that through new channels, consumers' information environment is altered sufficiently to affect their decision accuracy. Moreover, the results indicate that previous research may be overestimating the positive effect of mobile channel adoption on sales by disregarding changes in product return behavior.